BAHASA POSITIF DAN MOTIVASI MENULIS TEKS EKSPOSISI: STUDI KASUS IMPLEMENTASI HYPNOTEACHING PADA SISWA KELAS X - Erfandi; Asmoni; Khoirul Asiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of positive-suggestion-based hypnoteaching in expository text instruction and to interpret students’ responses to the practice in relation to their writing motivation. This study employed a qualitative approach with an interpretive case study design involving Grade 10 students SMA Islam Nurul Huda. Data were collected through classroom observations, semi-structured interviews with the teacher and students, students’ written reflections, and analysis of instructional documents and students’ written work. The data were analyzed using reflexive thematic analysis through the stages of data familiarization, coding, theme development, theme review, theme definition, and interpretive writing. The findings indicate that the use of positive language, realistic affirmations, gradual instructional guidance, and supportive feedback created a safer learning environment and encouraged students’ engagement. These practices strengthened students’ confidence, willingness to express ideas, persistence in completing writing tasks, and readiness to revise their texts. However, positive suggestions did not automatically increase motivation because their significance depended on the authenticity of the teacher’s language, the quality of teacher–student relationships, and the clarity of academic scaffolding. These findings confirm that hypnoteaching can be understood as supportive pedagogical communication that promotes students’ motivation to write expository texts.